Neosporosis and Visceral Leishmaniosis in a Dog in Central–West Brazil - Sena Bianca Ribas; Freitas Maria Sabrina de; Freitas Maria Natália de; Almeida Arleana do Bom Parto Ferreira de; Sousa Valéria Régia Franco (Acta Veterinaria)
Dogs act as definitive hosts for several diseases caused by protozoa, some of which are zoonotic. Due to their close contact with humans and other animals, they play a crucial role in the transmission of these diseases. Although infection with Neospora caninum or Leishmania infantum is not a determining factor for another, co-infection with these protozoa can aggravate clinical signs and increase the mortality rate. Though, there are reports of success in the treatment of neosporosis, the prognosis is generally considered unfavorable, especially in young dogs. The objective of this study is to report a case of infection by both protozoa in a dog treated at a university veterinary hospital, highlighting the clinical remission of nervous signs of neosporosis after treatment with the combination of sulfadoxine and clindamycin, followed by reduction of clinical signs of canine leishmaniasis (CanL) with treatment with miltefosine and allopurinol. Despite the worse prognosis for co-infection with N. caninum and L. infantum, the dog presented remission of neurological signs and a reduction in parasite load and clinicopathological signs associated with CanL.